Menuju UKM Sehat Melalui Sosialisasi Pengelolaan Keuangan dan Pelatihan Pembukuan Sederhana di Dusun Kranon - Sastika Devi, Apriliana; Nafiati, Lu’lu (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2022)
Kranon is one of the hamlets located in the Nitikan Village Rukun, Sorosutan Village. The majority of the people have SMEs businesses. The high level of business activities carried out is not accompanied by knowledge related to the factors that support their business activities such as management, recording, and financial reporting so that business actors only focus on profits without paying attention to other supporting factors. This is done in order to improve SMEs' financial management, recording, and reporting so that business actors can find out the financial condition of their business. With this, it is expected to be able to realize the financial condition of healthy Small and Medium Enterprises (SMEs). The community service activities carried out some programs. One of whic is socializing the importance of financial management and simple bookkeeping training which is expected to provide outputs in the form of simple financial reports for business units. The activities carried out in Kranon Hamlet can increase knowledge related to financial literacy for Small and Medium Enterprises (SMEs) through financial management, recording, and reporting. Small and Medium Enterprises (SMEs) ultimately have an understanding that bookkeeping is very important to do to prepare financial reports which can later be used as an illustration to assess the condition of their business and financial statement information can be used for decision making.